ADAPTIVE REUSE PADA BANGUNAN RESTORAN ROEMAH NENEK - Febry Maharlika; Achmad Rifai (Narada : Jurnal Desain dan Seni, 2023)
This research aims to explain the application of the adaptive reuse concept to one of the heritage buildings in Bandung, namely Roemah Nenek Restaurant. The concept of adaptive reuse is used for sustainability in ecological, economic and social aspects. But of course, it must be able to fulfill the existing conservation ethics. Therefore, this research aims to explain the application of adaptive reuse through five criteria of conservation ethics, namely sustainability, viability, integrity, continuity and authenticity in the Roemah Nenek Restaurant building. The research method used is descriptive-analytic method. Data collection was carried out through field surveys by conducting direct observations located on Jl. Taman Cibeunying Selatan No.47, Cihapit, Kec. Bandung Wetan, Bandung City, West Java. The result of this research is the application of adaptive reuse in the Roemah Nenek Restaurant building fulfills conservation ethics by maintaining the original structure of the building and maintaining historical or social memory even though in a different way.